TAKING INTO ACCOUNT SEXUAL DETERMINATION IN THE EDUCATIONAL PROCESS: SEXUAL AND GENDER EDUCATION (END OF XX - BEGINNING OF XXI CENTURY) - Doronina Т.О. (Pedagogy of Higher and Secondary Education, 2022)
The basic approaches to define the essence of the sexual education issued in pedagogics by the beginning of the XXI century are considered in the article. On the basis of the presented tendencies the position about conceptual difference between the theory of sexual and gender education is proved.